CD73 expression on extracellular vesicles derived from CD4+CD25+Foxp3+ T cells contributes to their regulatory function. Issue 9 (15th July 2013) - Smyth, Lesley Ann; Ratnasothy, Kulachelvy; Tsang, Julia Y. S.; Boardman, Dominic; Warley, Alice; Lechler, Robert; Lombardi, Giovanna
<x xml:space="preserve">Abstract</x> CD4+CD25+Foxp3+ Treg cells maintain immunological tolerance. In this study, the possibility that Treg cells control immune responses via the production of secreted membrane vesicles, such as exosomes, was investigated. Exosomes are released by many cell types, including T cells, and have regulatory functions. Indeed, TCR activation of both freshly isolated Treg cells and an antigen‐specific Treg‐cell line resulted in the production of exosomes as defined morphologically by EM and by the presence of tetraspanin molecules LAMP‐1/CD63 and CD81. Expression of the ecto‐5‐nucleotide enzyme CD73 by Treg cells has been shown to contribute to their suppressive function by converting extracellular adenosine‐5‐monophosphate to adenosine, which, following interaction with adenosine receptors expressed on target cells, leads to immune modulation. CD73 was evident on Treg cell derived exosomes, accordingly when these exosomes were incubated in the presence of adenosine‐5‐monophosphate production of adenosine was observed. Most importantly, CD73 present on Treg cell derived exosomes was essential for their suppressive function hitherto exosomes derived from a CD73‐negative CD4+ T‐cell line did not have such capabilities. Overall our findings demonstrate that CD73‐expressing exosomes produced by Treg cells following activation contribute to their suppressive activity through the production of adenosine.